Karl Barth on the Irresistible Nature of Grace - Torrance, Andrew (Journal of reformed theology, 2016)
Few issues have been as divisive for the contemporary church as the doctrine of irresistible grace. In the debates surrounding this doctrine, there has been an overwhelming tendency for theologies of grace to focus on the effects that grace has on particular human beings. Alongside this tendency, there has arisen a danger that we forget that God’s grace is God’s grace; that it is God’s free, personal, and beneficent disposition and action. In this article, I turn to Karl Barth to consider a way forward for interpreting the irresistible nature of grace that does not focus on its effectuality but on its theocentric, participative, and covenantal character.